Contributions of small‐scale and longline fishing to sea turtle mortality in the Solomon Islands - Christopher Brown; Richard Hamilton; Simon Vuto; Willie Atu; Rosalie Masu; Christain Ramofafia; Pete Waldie (Conservation Letters)
Abstract A focus of sea turtle management has been reducing bycatch in commercial fisheries, but sustainable harvest for consumption is also an important objective in many nations. Identifying how much different fisheries contribute to turtle mortality could help focus limited management resources. We estimated national scale turtle catches for two fisheries in the Solomon Islands: a small‐scale reef fishery where turtles are caught for food and sale, and an offshore longline fishery where turtles are bycatch. The footprint of the longline fishery spanned the entire exclusive economic zone of the Solomon Islands and was 67 times bigger than the footprint of the small‐scale fishery. The median catch summed across both fisheries was ∼12,000 turtles in 2018, with 85%–97% of that catch in the small‐scale fishery. We suggest that turtle management in the Solomon Islands, a nation with globally significant turtle breeding populations, should focus on sustainable management of small‐scale coastal fisheries.